El dinero electrónico como herramienta financiera idónea para alcanzar una mayor inclusión financiera y económica en el Ecuador - Suárez Zambrano, Alejandra Yarley (2015)
This research addresses the issue of electronic money as important to make possible further financial and economic inclusion in Ecuador financial tool. The document also contains a detailed study of the results obtained by applying the system of electronic money in other economies, such as Japan, Kenya and Paraguay. At the same time, programs of financial and economic inclusion in other parts of the world were studied, achieving its derivatives determine the importance of governments to design and implement programs of economic and financial education from primary, secondary and higher education. All this in the context of achieving a significant level of financial and economic education that allows society to have responsible citizens with critical judgment and discretion, with an objective view of things and events around you in your environment and an ethical and moral training for the decisions that will improve their individual and collective welfare. From this perspective it can be seen-on the basis of documentary research realizada- in effect, countries that have implemented this virtual currency circulation, have obtained high levels of financial inclusion and important advances in economic education. Among the research methods used it has the deductive-analytic, since the study began reviewing situations from a (general) international context and then focus it at national level; ie placement in a particular plane, as is the case of Ecuador. Consequently, among the primary sources of research there are scientific articles and academic, newspapers and magazines, documentaries and NGO studies, s. In what has to do with the field research, interviews were conducted with professionals in the economy, they gave their views on the desirability or otherwise of the implementation of the electronic money system in Ecuador; while, along with the documentary information gathered from the examples of other countries, it can be concluded on the feasibility of the use of electronic money as a tool of economic and financial inclusion in the country.